The network is your customer : five strategies to thrive in a digital world - Rogers, David L. (New Haven, Conn. ; London : Yale University Press, 2013)
Whether shoppers, charitable donors, or election voters, today's customers are harnessing digital tools to connect to, communicate with, and contribute to businesses. This book shows business owners and company leaders how to think strategically about customer networks and harness their power to create new opportunities for any organization.
Includes bibliographical references and index.
Keywords: Business networks; Social networks; Digital media -- Social aspects; Digital media -- Economic aspects; Strategic planning